Genetic aetiology distribution of 398 foetuses with congenital heart disease in the prenatal setting. (7th December 2022) - Yi, Tong; Hao, Xiaoyan; Sun, Hairui; Zhang, Ye; Han, Jiancheng; Gu, Xiaoyan; Sun, Lin; Liu, Xiaowei; Zhao, Ying; Guo, Yong; Zhou, Xiaoxue; He, Yihua
Abstract: Aims: Copy number variant‐sequencing (CNV‐seq) and exome sequencing (ES) have been used as powerful tools in understanding the role of genetic variants in congenital heart diseases (CHDs). A few previous large cohort studies have utilized CNV‐seq and ES to investigate prenatally diagnosed CHD. Here, we sought to determine the value of CNV‐seq and ES for genetic evaluation of foetal CHDs. Methods and results: We recruited 398 pregnant women diagnosed with CHDs between 8 January 2017 and 30 November 2020. CNV‐seq and ES were performed on foetal and parent samples. CHD cases were classified following the guidelines of the International Paediatric and Congenital Cardiac Code and the Tenth and Eleventh Revisions of the International Classification of Diseases. Data on aneuploids (AUP), pathogenic CNVs (pCNVs), and single nucleotide variants (SNVs) were collected and compared, following appropriate procedures. We identified genetic abnormalities in 129 (32.41%) foetuses. These abnormalities included AUP (10.80%), pCNVs (13.32%), and SNVs (8.04%). ES analysis yielded higher SNVs in cases without AUP or pCNVs. Non‐isolated CHDs were associated with higher genetic abnormalities than isolated CHDs, mainly due to AUP differences between the two groups. The prevalence of genetic defects was the highest in foetuses with atrioventricular septal defects (AVSD), left ventricular outflow tract obstruction (LVOTO), and conotruncal defects (CTD). AVSD and anomalies of atrioventricular junctions and valves were associated with AUP abnormalities. CTD, anomalies of extrapericardial arterial trunks, and anomalies of the ventricular outflow tracts were the most common CHD categories diagnosed using CNVs. The most common CHDs associated with single ventricle (SV) abnormalities were heterotaxy (Hex) (14.89%), LVOTO (14.58%), and ventricular septal defect (VSD) (26.67%, 4/15). Although the ES yields were higher than CNV‐seq for VSD (44.4%, 4/9), LVOTO (20%, 7/35), Hex (14.89%, 7/47), and CTD (9.1%, 11/121), its diagnostic yield did not increase for SV (6.7%, 1/15), AVSD (3.8%, 1/26), or right ventricular obstruction defects (2.6%, 1/38). The most common mutations were observed in KMT2D, CHD7, and NOTCH1 . Conclusions: To our knowledge, this is the largest cohort study to investigate the incidence of SNVs using ES in foetal CHD. CNV‐seq and ES identified genetic abnormalities in nearly 1/3 of foetal CHD cases. Thus, CNV‐seq and ES can provide clinically relevant information for pregnancy management.